The Use of Biopsy and “No-Biopsy” Approach for Diagnosing Paediatric Coeliac Disease in the Central European Region - Petra Riznik; Márta Balogh; Piroska Bódi; Luigina De Leo; Jasmina Dolinsek; Ildikó Guthy; Judit Gyimesi; Ágnes Horváth; Ildikó Kis; Martina Klemenak; Berthold Koletzko; Sibylle Koletzko; et al. (Gastroenterology Research and Practice)
Objectives. The current European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) guidelines introduced the option to diagnose coeliac disease (CD) in children and adolescents without upper endoscopy if the defined criteria are met. The aim of our study was to evaluate how frequently paediatric gastroenterologists in Central Europe used the “no-biopsy” approach and how often the duodenal biopsy could have been omitted. Methods. Medical records of patients aged<19 years diagnosed with CD in 2016 from five European countries were analysed, focusing on levels of transglutaminase antibodies (TGA) at the time of diagnosis and on whether the diagnosis was confirmed using duodenal biopsy or “no-biopsy” approach. Clinical presentation and delays until final diagnosis were analysed according to diagnostic approach. Results. Data from 653 children (63.9% female, median age: 7 years, range: 7 months-18.5 years) from Croatia, Hungary, Germany, Italy, and Slovenia were analysed. One fifth (n=134) of included children were asymptomatic at diagnosis. Of 519 symptomatic children, 107 (20.6%) were diagnosed by the “no-biopsy” approach. Out of the remaining 412 children who underwent duodenal biopsies, 214 (51.9%) had TGA≥10 times upper level of normal (ULN) and would have been eligible for the “no-biopsy” approach. Signs and symptoms of malabsorption were more frequent in children diagnosed without duodenal biopsies. There were no differences in diagnostic delays with respect to the diagnostic approach. Conclusion. In this cohort, about 60% of symptomatic CD patients could have been diagnosed without duodenal biopsies. The aim of the “no-biopsy” approach was to make the diagnostic procedure less challenging without compromising its reliability. However, this option was applied only in 20%, in spite of fewer burdens to the family and reduced costs. The reasons for this discrepancy are unknown. Physicians should be made more aware about the reliability of CD diagnosis without biopsies when the ESPGHAN guidelines for CD diagnosis are followed.